The usability of training management system for teachers’ professional development: a preliminary study - Mohd, Noradlina; Azmi Murad, Masrah Azrifah (Secholian Publication, 2022)
The usability study of the Ministry of Education’s Training Management System (SPLKPM) is a preliminary study conducted by the researcher to determine the rationale and analysis of research needs regarding system usage behaviour among teachers. The purpose of this study is to assess the system's usability in the management of in-service teacher training. SPLKPM serves as a platform that records and stores training data and credit point reporting for all Ministry of Education (MoE) staff members based on 13 activities outlined in continuous professional development credit points (MyPBB). The respondents for this study were in-service teachers who are also regular users of SPLKPM. A total of 32 respondents provided feedback that was randomly distributed through several mediums; emails and mobile messaging apps. The study found that the existing system has a usability score of 45.9, compared to the average of 68, indicating that it requires improvement and that a comprehensive analysis of the factors that influence system use should be done. In conclusion, most teachers believe that the system needs to be improved to facilitate more frequent recording and use.